Electrophysiological Correlates of the Effect of Task Difficulty on Inhibition of Return - Li, Ai-Su; Miao, Cheng-Guo; Han, Yu; He, Xun; Zhang, Yang (Frontiers in Psychology, 2018)
Inhibition of return (IOR) refers to slower responses to targets occurred at the previously attended location than to those at control locations. Several previous studies have examined the impact of task difficulty on IOR. However, in those studies, the low-level characteristics of target stimuli (e.g., size, color, and luminance) have not been matched across different levels of task difficulty and thus are likely confounded with task difficulty. Hence, so far whether and how the task difficulty starts to modulate IOR remains largely unknown. Here we utilized the event-related potentials (ERP) technique in combination with the cue-target paradigm to tackle this question. After matching the target stimuli in size, color, and luminance, we effectively manipulated the task difficulty by changing the gap position in relative to the horizontal meridian of an outline rectangle. Behaviourally, IOR in reaction times was observed in all difficulty conditions, but only the medium condition exhibited IOR in the accuracy. Electrophysiologically, ERP components N1/P2, exhibited a significant difference between the cued and the uncued conditions in the easy, and the hard conditions but showed a much smaller difference in the medium condition, demonstrating that the modulation of task difficulty on IOR stems from the perceptual and post-perceptual processing stage.